PENDIDIKAN KARAKTER MELALUI PEMBIASAAN AKHLAK MULIA: Studi SMP Muhammadiyah 1 Gombong - S Siti (MAMBA'UL 'ULUM, 2023)
This study aims to identify programs to strengthen character education in high schools through the habituation of noble character. This research uses descriptive qualitative method. The research was conducted at SMP Muhammadiyah 1 Gombong. Data collection was carried out by observation, interviews, and documentation studies. Data analysis was carried out with the stages of inventorying data, classifying data, analyzing data, and formulating conclusions. The results of this study indicate that the character education strengthening program at SMP Muhammadiyah 1 Gombong is by integrating the learning process with the habituation of noble moral values in everyday life; An important finding from this study is that the habituation of noble character implemented in secondary schools is an effective model for strengthening the character of students.